RNA modification writers pattern in relation to tumor microenvironment and prognosis in prostate cancer - Cheng, Xu; Yi, Xuanzi (Frontiers in Genetics, 2023)
Background RNA modifications are important in the study of epigenetic regulatory mechanisms in immune responses and tumorigenesis. When RNA writers are mutated or disrupted in expression, the genes associated with the pathways they modify are also disrupted and can activate or repress related pathways, affecting tumorigenesis and progression. However, the potential role of RNA writers in prostate cancer is unclear. Methods Based on data from three datasets, we describe 26 RNA writers that mediate gene expression and genetic mutation in prostate cancer and assess their expression patterns in 948 prostate cancer samples. Using principal component analysis algorithms, the RM Score was developed to quantify the RNA modification patterns of specific tumors. Results Two different categories were determined by unsupervised clustering methods, and survival analysis showed significant differences in OS prognosis between these 2 categories. Differentially expressed genes between the different categories were detected and the RNA writers-mediated scoring model RM_Score were constructed based on this. Also, the RM_Score was analyzed in relation to clinical characteristics, immune infiltration level, drug response, and efficacy of chemotherapy and immunotherapy. Those results confirm that multilayer alterations in epitope-modified RNA writers are associated with patient prognosis and with immune cell infiltration characteristics. Finally, we examined differentially expressed mRNA, lncRNA and miRNA between high and low RM_Score groups, based on which a ceRNA regulatory network was constructed. Conclusions This work is a comprehensive analysis of modified writers in prostate cancer and identified them to have a role in chemotherapy and immunotherapy.